Prevalence and predictors of hospital prealerting in acute stroke: a mixed methods study. Issue 7 (23rd February 2016) - Sheppard, J P; Lindenmeyer, A; Mellor, R M; Greenfield, S; Mant, J; Quinn, T; Rosser, A; Sandler, D; Sims, D; Ward, M; McManus, R J
Abstract : Background: Thrombolysis can significantly reduce the burden of stroke but the time window for safe and effective treatment is short. In patients travelling to hospital via ambulance, the sending of a 'prealert' message can significantly improve the timeliness of treatment. Objective: Examine the prevalence of hospital prealerting, the extent to which prealert protocols are followed and what factors influence emergency medical services (EMS) staff's decision to send a prealert. Methods: Cohort study of patients admitted to two acute stroke units in West Midlands (UK) hospitals using linked data from hospital and EMS records. A logistic regression model examined the association between prealert eligibility and whether a prealert message was sent. In semistructured interviews, EMS staff were asked about their experiences of patients with suspected stroke. Results: Of the 539 patients eligible for this study, 271 (51%) were recruited. Of these, only 79 (29%) were eligible for prealerting according to criteria set out in local protocols but 143 (53%) were prealerted. Increasing number of Face, Arm, Speech Test symptoms (1 symptom, OR 6.14, 95% CI 2.06 to 18.30, p=0.001; 2 symptoms, OR 31.36, 95% CI 9.91 to 99.24, p<0.001; 3 symptoms, OR 75.84, 95% CI 24.68 to 233.03, p<0.001) and EMS contact within 5 h of symptom onset (OR 2.99, 95% CI 1.37 to 6.50 p=0.006) were key predictors of prealerting but eligibility for prealert as a whole was not (OR 1.92, 95% CI 0.85 to 4.34 p=0.12). In qualitative interviews, EMS staff displayed varying understanding of prealert protocols and described frustration when their interpretation of the prealert criteria was not shared by ED staff. Conclusions: Up to half of the patients presenting with suspected stroke in this study were prealerted by EMS staff, regardless of eligibility, resulting in disagreements with ED staff during handover. Aligning the expectations of EMS and ED staff, perhaps through simplified prealert protocols, could be considered to facilitate more appropriate use of hospital prealerting in acute stroke.